2005
DOI: 10.1161/01.str.0000170641.01047.cc
|View full text |Cite
|
Sign up to set email alerts
|

A Matrix Metalloproteinase Protein Array Reveals a Strong Relation Between MMP-9 and MMP-13 With Diffusion-Weighted Image Lesion Increase in Human Stroke

Abstract: Background and Purpose-Matrix metalloproteinases (MMPs) are involved in tissue destruction produced by the neuroinflammatory response that follows ischemic stroke. In the present study we use an MMP array to investigate the blood levels of several MMPs in stroke patients and its relation with brain tissue damage and neurological outcome. Methods-Twenty-four patients with middle cerebral artery occlusion who received thrombolytic therapy were included.Blood samples were drawn before tissue plasminogen activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 32 publications
3
123
0
5
Order By: Relevance
“…A larger infarct volume might also lead to a greater inflammatory response to the ischemic tissue. This is supported by studies showing elevated inflammatory markers are associated with infarct volume, including TNF-α [53], IL-6 [54,55], ICAM-1 [53], MMP-2 and MMP-9 [53,56].…”
Section: Biomarkers Of Final Infarct Volume and Outcomementioning
confidence: 71%
See 1 more Smart Citation
“…A larger infarct volume might also lead to a greater inflammatory response to the ischemic tissue. This is supported by studies showing elevated inflammatory markers are associated with infarct volume, including TNF-α [53], IL-6 [54,55], ICAM-1 [53], MMP-2 and MMP-9 [53,56].…”
Section: Biomarkers Of Final Infarct Volume and Outcomementioning
confidence: 71%
“…IL-6 levels >21.5 pg/ml in plasma and 6.3 pg/ml in CSF predict END [54]. MMP-9 and MMP-13 independently predict lesion volume expansion in ischemic stroke [56]. CSF nitric oxide levels >5umol/ml also predict END [70].…”
Section: Biomarkers To Predict Early Neurological Deteriorationmentioning
confidence: 98%
“…However, the study by Rosell et al (2005) has shown no correlation between the plasma levels of MMP-1, -2, -3, -8, and -10 and the extent of the lesion. In a subset of MCAO mice injected with the MMP-activatable probe, multiparametric MRI was performed immediately and 24 h after reperfusion to assess the development of the ischemic lesion.…”
Section: Discussionmentioning
confidence: 94%
“…Matrix metalloproteinase-9 is detected in human brain tissue sections after ischemic and hemorrhagic strokes (Rosell et al, 2006). Plasma levels of MMP-9 are increased in patients with acute stroke and correlate with the clinical outcome (Montaner et al, 2003a;Rosell et al, 2005). Patients with higher plasma MMP-9 levels are also more likely to undergo hemorrhagic transformation after tissue plasminogen activator treatment (Montaner et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported using an MMP protein array that high levels of MMP-9 and MMP-13, also known as collagenase-3, are involved in diffusion-weighted image lesion growth. 29 It remains to be clarified whether MMP-13 is involved in the BBB disruption.…”
Section: Introductionmentioning
confidence: 99%